Fuel Consumption And Fuel Economy Of Hydraulic Hybrid Vehicle - Tharumaalingam, Vimalraj (Universiti Sains Malaysia, 2022)
This study focuses on the fuel economy performance of the Through-The-Road (TTR) Hydraulic Hybrid Vehicle (HHV). TTR is a type of parallel architecture that connects the conventional drive train and the hybrid drive train through the road. The hydraulic hybrid drive train that was in the vehicle was used to be tested in the experiment. An Arduino programme system for through-the-road hydraulic hybrid was developed to determine the fuel consumption and fuel economy of the vehicle. The fuel consumption is measured by weighing the fuel tank before and after each run of similar urban drive cycle that has same driver and circuit for testing. The through-the-road hydraulic hybrid fuel consumption test was separated into two which is with the air conditioner on (ACON) and with the air conditioner off (ACOF). By using the data from the fuel consumption test, the fuel economy is obtained where it is compared between the original Perodua Myvi mode, conventional hybrid myvi mode and the hybrid myvi hybrid mode. Thus, the test shows that for ACON mode, the hydraulic hybrid mode provides about 8% fuel economy improvement compared to the conventional hybrid mode. While ACON original Myvi mode has 41% better fuel economy than ACON hybrid Myvi hybrid mode. In addition, for the ACOF mode, ACOF original Myvi mode has 78% higher fuel economy than ACOF hybrid mode. Finally, the data was also compared between the ACON mode and ACOF mode where the fuel economy of ACON original Myvi mode was 24% better than ACOF hybrid Myvi hybrid mode. This is because of the heavy weight of the hydraulic components that are in the Hybrid Myvi which consumes more fuel to propel the vehicle.